THE INFLUENCE OF CUSTOMER REVIEWS, EASE OF TRANSACTIONS, AND CUSTOMER TRUST ON ONLINE PURCHASE DECISION OF HALAL PRODUCT - Abdul Rosid, Afif (Journal of Management and Islamic Finance, 2024)
The phenomenon of changing people's behavior in shopping has undergone major changes. People are now starting to switch to shopping efficiently and practically. A shift in people's behavior from buying by coming directly to the store to buying online or through e-commerce. Changes in people's behavior in shopping will certainly affect consumer purchasing decisions in buying a product. This study aims to explain how the influence of customer reviews, ease of transactions and consumer confidence in purchasing halal products online. Samples were taken 150 respondents randomly from the population using simple random sampling technique. Data were analyzed using multiple linear regression analysis. The results of this study are that the influence of customer reviews influences the decision to purchase halal products online. Meanwhile, convenience has no effect on purchasing decisions for halal products online. Meanwhile, consumer trust is the most influential variable on purchasing decisions for halal products online. Based on the results of this study, researchers suggest marketplaces to continue to increase consumer confidence by adding several facilities.